On the use of interpolated second-order polynomials for efficient filter design in programmable downconversion. - Oh, H.J (IEEE Journal on selected areas in communications)
Interpolated second-order polynomials (ISOPs) are proposed to design efficient cascaded integrator-comb (CIC)-based decimation filters for a programmable downconverter. It is shown that some simple ISOPs can effectively reduce the passband droop caused by CIC filtering with little degradation in aliasing attenuation. In addition, ISOPs are shown to be useful for simplifying halfband filters that usually follow CIC filtering. As a result, a modified halfband filter (MHBF) is introduced which is simpler than conventional halfband filters. The proposed decimation filter for programmable downconverter is a cascade of a CIC filter, an ISOP, MHBFs, and a programmable finite impulse response filter. A procedure for designing the decimation filter is developed. In particular, an optimization technique that simultaneously designs the ISOP and programmable FIR filters is presented. Design examples demonstrate that the proposed method leads to more efficient programmable downconverters than existing ones